Clinical Features and Therapeutic Response in Women Meeting Criteria for Presumptive Treatment for Pelvic Inflammatory Disease Associated With Mycoplasma genitalium. Issue 2 (February 2019) - Latimer, Rosie L.; Read, Tim R.H.; Vodstrcil, Lenka A.; Goller, Jane L.; Ong, Jason J.; Fairley, Christopher K.; Hocking, Jane S.; Bradshaw, Catriona S.
Abstract : Background: There are limited published data describing clinical features and therapeutic response in women meeting the criteria for presumptive treatment of pelvic inflammatory disease associated with Mycoplasma genitalium (MG-PID). The MG-PID has been reported to respond poorly to standard PID treatment regimens and while moxifloxacin is recommended in several treatment guidelines, published data to support its use are scant. Methods: We conducted a retrospective study of women at Melbourne Sexual Health Centre between 2006 and 2017, who met the Centers for Disease Control and Prevention criteria for presumptive treatment of PID, and had MG detected as the sole pathogen. Clinical and laboratory characteristics of MG-PID were compared to cases of chlamydial PID (CT-PID) by multivariable analysis. Microbiological and clinical cure following moxifloxacin and standard PID treatment was determined for women with MG-PID who returned for test of cure between 14 and 120 days. Results: Ninety-two patients with MG-PID were compared with 92 women with CT-PID. The MG-PID was associated with increased lower abdominal tenderness (adjusted odds ratio, 2.29; 95% confidence interval [CI], 1.14–4.60), but a lesser vaginal polymorphonuclear response compared to CT-PID by multivariable analysis. Of the 92 women with MG-PID, 54/92 (59%) received moxifloxacin (10–14 days) and 37/54 had a test of cure between 14 and 120 days; 27/37 (73%) cases had a median of 7 days of a standard regimen containing doxycycline and metronidazole +/− azithromycin before moxifloxacin. Microbial cure following moxifloxacin was 95% (95% CI, 82–99%) and did not differ from standard therapy ( P = 0.948), however clinical cure was significantly higher following moxifloxacin (89%; 95% CI, 75–97%; P = 0.004)] although adverse effects were more common. Conclusions: Women meeting Centers for Disease Control and Prevention criteria for presumptive treatment of MG-PID did not significantly differ to those with CT-PID. Moxifloxacin was associated with higher rates of symptom resolution in women with PID, and although microbial cure was high, it did not differ between regimens. Abstract : Clinical features in women with Mycoplasma genitalium –associated presumptive pelvic inflammatory disease do not differ significantly to chlamydial pelvic inflammatory disease, and moxifloxacin is an effective treatment although side effects are common.